Type of the equiangular tight frames with \(n+1\) vectors in \(R^n\) - Arbabi Mohammad-Abadi, Somayeh; Najafi, Mohammad (International Journal of Applied Mathematical Research, 2012)
An equiangular tight frame (ETF) is a \(d ×Â n\) matrix that has orthogonal rows and unit-norm columns. ETFs have applications in communications, coding theory and quantum computing. In this paper we investigate type of ETFs that have \(n+1\) vectors in \(R^n\). Also we state the connection between these frames with the complete graphs that containing \(n+1\) vertices.